KOMUNIKASI SINGKAT: Penyakit Keriting Pada Tanaman Pepaya Di Bogor - Maria Ulfa Putri Yoeshinda; Widodo Widodo (Jurnal Fitopatologi Indonesia, 2014)
Papaya is widely grown and consumed in Indonesia as a favorite fruit. Since 2011, a new disease was reported in Bogor, i.e. leaf curl disease caused by Cladosporium cladosporioides.Therefore, a survey was conducted in Bogor to determine the status of leaf curl disease of papaya and to identify some agricultural practices that may affect disease development. Based on field observation conducted in Bogor, subdistricts Rancabungur and Sukaraja, it was evidenced that leaf curl disease has been widely spread, with disease incidence reached 87 % and 96%, respectively and disease severity in both areas reached 24–28%. Although disease severity was not different, disease incidence was generally lower in papaya field cultivating var. Caliporan (medium type fruit)or in monoculture cropping system compared to those cultivating var. Bangkok (large type fruit) or multiple cropping system. Other cultivated practices did not seem to cause significant effect on disease incidence and severity.